Pengaruh Kerjasama Tim, Motivasi Kerja dan Lingkungan Kerja Terhadap Prestasi Kerja Karyawan pada Bank Sumsel Babel Syariah Cabang Palembang - Andi Susanti; Endah Dewi Purnamasari; Roswaty Roswaty (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study aims to determine the effect of teamwork, work motivation and work environment on employee performance in Bank Sumsel Babel Syariah Palembang Branch. This study uses primary data whose data collection uses questionnaires, interviews and observations. In this study, researchers used quantitative analysis, multiple linear regression analysis and coefficient of determination analysis using SPSS 26. The population in this study were all employees of Bank Sumsel Babel Syariah Palembang Branch total 50. The research results obtained using t test and F test show that teamwork has a positive but insignificant effect on employee performance, work motivation and work environment have a positive and significant effect on employee performance, and teamwork, work motivation and work environment have a positive and significant effect on employee performance simultaneously. In the coefficient of determination test, the data results obtained amounted to 73.7%, which can be explained by the influence of teamwork, work motivation and work environment on employee performance, while the remaining 26.3% can be explained by the influence of other variables not examined by the author.